The effect of 1, 25(OH)2 D3 (calcitriol) alone and in combination with all-trans retinoic acid on ROR-γt, IL-17, TGF-β, and FOXP3 gene expression in experimental autoimmune encephalomyelitis. (16th March 2018) - Parastouei, Karim; Mirshafiey, Abbas; Eshraghian, Mohammad Reza; Shiri-Shahsavar, Mohammad Reza; Solaymani-Mohammadi, Farid; Chahardoli, Reza; Alvandi, Ehsan; Saboor-Yaraghi, Ali Akbar
Abstract : Objectives: It has been shown that calcitriol and all-trans retinoic acid (ATRA) have modulatory effects on the immune system. The present study investigates the synergistic effects of combination treatment of calcitriol and ATRA in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS). Methods : The mice were allocated to four preventive groups, each consisting of eight animals, ATRA (250 μg/mouse), calcitriol (100 ng/mouse), combination of ATRA and calcitriol (125 μg/mouse and 50 ng/mouse) and vehicle groups. EAE was induced by MOG35-55 peptide in female C57BL/6 mice. Treatments were initiated at day 1 before immunization and continued every other day throughout the study until the day 21 post-immunization. Splenocytes were isolated from EAE-induced mice and the expression of retinoic acid receptor-related orphan receptor gamma t (ROR-γt), Interleukin-17 (IL-17), transforming growth factor beta (TGF-β), and forkhead box P3 (FOXP3) genes was measured using real-time polymerase chain reaction. Results : The expression of FOXP3 and TGF-β genes in the splenocytes of combination-treated and calcitriol alone-treated mice was significantly increased compared to vehicle group ( P < 0.05). The expression of ROR-γt and IL-17 genes in the splenocytes of ATRA, calcitriol and combination- treated mice was significantly reduced compared to those of vehicle- treated mice ( P < 0.05). The relative expression level of ROR-γt was significantly ( P < 0.05) lower in the combination group than in the mice treated by ATRA or calcitriol alone. Discussion : This study demonstrated that treatment with combination of calcitriol and ATRA can be considered as a new strategy for MS prevention and treatment. GRAPHICAL ABSTRACT: